Assessing the convergent validity between the automated emotion recognition software Noldus FaceReader 7 and Facial Action Coding System Scoring - Skiendziel, Tanja; Rösch, Andreas; Schultheiss, Oliver (PLoS ONE, 2019)
This study validates automated emotion and action unit (AU) coding applying FaceReader 7 to a dataset of standardized facial expressions of six basic emotions (Standardized and Motivated Facial Expressions of Emotion). Percentages of correctly and falsely classified expressions are reported. The validity of coding AUs is provided by correlations between the automated analysis and manual Facial Action Coding System (FACS) scoring for 20 AUs. On average 80% of the emotional facial expressions are correctly classified. The overall validity of coding AUs is moderate with the highest validity indicators for AUs 1, 5, 9, 17 and 27. These results are compared to the performance of FaceReader 6 in previous research, with our results yielding comparable validity coefficients. Practical implications and limitations of the automated method are discussed.
CRIS-Team Scopus Importer:2019-10-29

Enhancing Congruence between Implicit Motives and Explicit Goal Commitments: Results of a Randomized Controlled Trial - Roch, Ramona; Rösch, Andreas; Schultheiss, Oliver (Frontiers in Psychology, 2017)

Implicit motives: Current topics and future directions - Schultheiss, Oliver; Rösch, Andreas; Rawolle, Maika; Kordik, Annette; Graham, Stacie C. (The decade ahead : theoretical perspectives on motivation and achievement, 2010)

Implicit motives predict affective responses to emotional expressions - Rösch, Andreas; Stanton, Steven J.; Schultheiss, Oliver (Frontiers in Psychology, 2013)
We explored the influence of implicit motives and activity inhibition (AI) on subjectively experienced affect in response to the presentation of six different facial expressions of emotion (FEEs; anger, disgust, fear, happiness, sadness, and surprise) and neutral faces from the NimStim set of facial expressions (Tottenham et al., 2009). Implicit motives and AI were assessed using a Picture Story Exercise (PSE) (Schultheiss et al., 2009b). Ratings of subjectively experienced affect (arousal and valence) were assessed using Self-Assessment Manikins (SAM) (Bradley and Lang, 1994) in a sample of 84 participants. We found that people with either a strong implicit power or achievement motive experienced stronger arousal, while people with a strong affiliation motive experienced less arousal and less pleasurable affect across emotions. Additionally, we obtained significant power motive × AI interactions for arousal ratings in response to FEEs and neutral faces. Participants with a strong power motive and weak AI experienced stronger arousal after the presentation of neutral faces but no additional increase in arousal after the presentation of FEEs. Participants with a strong power motive and strong AI (inhibited power motive) did not feel aroused by neutral faces. However, their arousal increased in response to all FEEs with the exception of happy faces, for which their subjective arousal decreased. These differentiated reaction patterns of individuals with an inhibited power motive suggest that they engage in a more socially adaptive manner of responding to different FEEs. Our findings extend established links between implicit motives and affective processes found at the procedural level to declarative reactions to FEEs. Implications are discussed with respect to dual-process models of motivation and research in motive congruence. © 2013 Rösch, Stanton and Schultheiss.
Keywords: Activity inhibition; Affect; Arousal; Emotion; Implicit motives; Inhibited power motive; Valence

Implicit motives show sex-dimorphic associations with digit ratio - Schultheiss, Oliver; Frisch, Miriam; Özbe, Dominik; Oßmann, Anna; Schultheiss, Maria; Rösch, Andreas (Motivation Science, 2019)

Motivation as a natural linchpin between person and situation - Schultheiss, Oliver; Kordik, Annette; Kullmann, Jennifer S.; Rawolle, Maika; Rösch, Andreas (Journal of research in personality, 2009)
Keywords: Motivation; Alliesthesia; Incentive; Implicit motive

Motivation - Schultheiss, Oliver; Strasser, Alexandra; Rösch, Andreas; Kordik, Annette; Graham, Stacie C. (Encyclopedia of human behavior, 2012)

Salivary progesterone is associated with reduced coherence of attentional, cognitive, and motivational systems - Schultheiss, Oliver; Patalakh, Mariya; Rösch, Andreas (Brain and cognition, 2012)
Implicit motives represent nonconsciously represented dispositions to seek specific classes of incentives and to avoid corresponding classes of disincentives. Growing evidence suggests that the implicit power motive is associated with basal levels and reactivity of the gonadal steroid hormones testosterone in men and estradiol in women. It is also associated with increased release of stress hormones (cortisol, norepinephrine) in response to dominance challenges and social defeat. The implicit affiliation motive is linked to the release of progesterone: increases in progesterone are followed by increases in affiliation motivation, and arousal of affiliation motivation is associated with concurrent or subsequent progesterone increases. There is limited evidence for a role of vasopressin in achievement motivation. These findings point to a key role of the hypothalamus for implicit motives, a role that is consistent with the existence of function-specific nuclei within this brain area.
Keywords: Attention networks; Gonadal steroids; Motivation; Referential competence; Personal goals; Implicit motives; Hemispheric function

The implicit need for power predicts recognition speed for dynamic changes in facial expressions of emotion - Donhauser, Peter; Rösch, Andreas; Schultheiss, Oliver (Motivation and Emotion, 2015)
Facial expressions of emotion (FEEs) have been portrayed as potent (dis-) incentives for power-motivated perceivers, because they signal the strength of a sender’s dominance (Stanton et al. in Implicit motives. Oxford University Press, New York, pp 245–278, 2010). Here, we tested the hypothesis that individuals with a high implicit power motive (nPower), who have a disposition to seek (emotional) impact on others, would be faster at recognizing FEEs than individuals low in nPower. In a task employing videos of morphed FEEs, which are gradually changing from neutral to either anger, joy or surprise, higher nPower predicted faster recognition of the displayed emotion as well as a tendency to misidentify joy as anger. Our findings suggest that one way through which people high in nPower are socially influential is their enhanced sensitivity to emotional signals in their social environment.
Keywords: Dominance; Emotion; Facial expressions; Implicit power motive